The Dual Role of Women in Employment in the Sinah Kasih Village Oil Palm Plantation - Putri, Widisyah; Malik, Rahman; Hidir, Achmad (Talenta Publisher, 2024)
Indonesia is theÂ countries with the largest palm oil producer in the world. Oil palm plants are one of the plantation crops that produce vegetable oil, which has become Indonesia's main and superior agricultural commodity. In the division of labor on plantations, there is still an imbalance between men and women. Women spend a lot of time in the garden and have to divide their time into housework. The dual roles experienced by women are very influential in the division of labor. This study presents the division of labor according to Harvard's division of labor. Women also work like men in oil palm plantations and women also play the role of housewives who take care of their husbands, children, and home. Meanwhile, men only work in industry, do not want to contribute to taking care of children and other household work, women do not get the same salary as men.